ANALISIS PENGARUH RASIO KEUANGAN DAN MARKET EFFECT UNTUK MEMPREDIKSI KEBANGKRUTAN BANK MENGGUNAKAN MODEL REGRESI LOGISTIK (Studi Pada Bank yang Terdaftar Di Bursa Efek IndonesiaPeriode 2008-2012) - Halim, Chandra; Savitri, Enni; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine the effect of accounting ratio and market effect for predicting bank’s bankruptcy with logistic regression model. Beside that this research also to measure the correction of bank’s bankruptcy predicting model.The research data is secondary data from annual financial statements of bank, annual report of bank, and bank’s stock history report. While the population in this research were all commercial banks in Indonesia that is still in operation and listing on the Indonesia stock exchange during the period of 2008-2012. By using the method of purposive sampling obtained 21 banks for the sample. The analysis is using logistic regression.The test results of logistic regression, model composed by accounting number and market effect.is illustratable probability of bank’s bankruptcy observe by the model fit result. Accounting numbers CAR, NPL and BOPO are significantly effect for probability of bank’s bankruptcy. By all of the variables in this research can explain 69% probability of bank’s bankruptcy and the other 31% explain by other variable. Predicting Accuracy of the model in this research is 95.2%.Keywords: Bank,PredictingBankruptcy, Accounting Ratios, Market Effect and Logistic Regression.